Clinical observation on effect of endurance exercise for elderly patients with maintenance hemodialysis (耐力运动在老年维持性血液透析患者中的应用效果观察) - HOU Ying (侯颖) (中西医结合护理)
Objective To investigate the effect of endurance exercise on motor function and metabolism-related indicators in elderly patients with maintenance hemodialysis. Methods Totally 30 elderly patients with maintenance hemodialysis who met the inclusion criteria were randomly divided into the study group (n=15)and control group (n=15). In the control group, the gymnastics exercise in supine position was carried out on dialysis days. In the study group, the gymnastics exercise combined with low-intensity aerobic training was carried out on dialysis days, and individualized exercise training was performed on non-dialysis days. The 6-Minute Waling Test (6MWT), Berg Balance Scale and hand grip strength measuring were used to assess the patients’ motor function. The primarily metabolism-related indicators were HGB, ABL, iPTH, Ca and PI. Results The 6MWT distance in the study group was higher than that in the control group after 42 weeks of dialysis(P＜0. 05). There was no significant difference in the score of Berg Balance Scale and value of hand grip strength between two groups after 42 weeks of dialysis(P＞0. 05). There was no significant difference in serum level of HGB, ALB, iPTH, Ca and PI between two groups after 42 weeks of dialysis(P＞0. 05). Conclusion Endurance exercise is safe and effective to improve the recovery of motor function and quality of life in the elderly patients with maintenance hemodialysis. More large-scale and high-quality studies should be done on to confirm the association between improved metabolism-related indicators and endurance exercise. (目的 观察耐力运动对老年维持性血液透析患者运动能力及相关代谢指标的影响。方法 选取符合纳入标准的老年维持性血液透析患者30例为研究对象, 采用随机数字表分成研究组(n=15)和对照组(n=15)。对照组在透析日仅进行卧位体操锻炼; 研究组在透析日进行卧位体操联合低强度有氧训练, 非透析日根据患者躯体功能状况设计个体化运动。运动能力评价包括6分钟步行试验(6MWT)、Berg平衡量表评分和握力数值; 实验室指标包括血红蛋白(HGB)、白蛋白(ABL)、全段甲状旁腺激素(iPTH)、血钙(Ca)和磷血(PI)。结果 42周后, 研究组6MWT距离较对照组提高明显, 差异有统计学意义(P＜0. 05); 研究组Berg平衡量表评分和握力数值较对照组有所提高, 但差异无统计学意义(P＞0. 05)。42周后, 两组HGB、ALB、iPTH、Ca、PI比较, 差异无统计学意(P＞0. 05)。结论 耐力运动安全、有效, 可以促进老年维持性血液透析患者肢体功能康复, 改善患者的生活质量。耐力运动对患者相关代谢指标的改善作用有待进一步开展大规模、高质量的临床研究证实。)